2022
DOI: 10.1021/acs.iecr.2c01178
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Surface Elution Mechanism of Citric Acid-Coordinated Hydroxyapatite Nanoparticles in Biological Solutions

Abstract: We clarified the surface elution behavior of citric acid (Cit) ions from Cit-coordinated europium­(III) ion (Eu3+)-doped hydroxyapatite (CEH) nanoparticles in three different biological solutions (i.e., phosphate buffer (PB), carbonate buffer (CB), and simulated body fluid (SBF)). Specifically, the elution behavior of Cit from the CEH nanoparticles in SBF was clarified as compared with the cases in PB and CB. Based on the elution results of Cit from the nanoparticles, two-stepwise (i.e., initially dramatic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…The substitutions at both sites are called type AB CHA [ 26 ]. CHA and CDHA particles have been investigated as nanocarriers for DDS based on the CHA/organic interface design [ 27 , 28 ].…”
Section: Bioceramic Particles and Surface Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…The substitutions at both sites are called type AB CHA [ 26 ]. CHA and CDHA particles have been investigated as nanocarriers for DDS based on the CHA/organic interface design [ 27 , 28 ].…”
Section: Bioceramic Particles and Surface Functionmentioning
confidence: 99%
“…CHA and CDHA particles have been investigated as nanocarriers for DDS based on the CHA/organic interface design [27,28].…”
Section: Carbonate-substituted Hydroxyapatitementioning
confidence: 99%
“…By exploiting the interaction between the ions located at the Ca sites in HAp and the carboxyl ions of the citric acid molecule, the synthesis of hybrid NPs can be achieved. [224][225][226][227][228][229][230] In order to utilize the aforementioned nanomaterial system for specific cell visualization, the authors added citrate ions during the synthetic process for substituting Eu 3+ with the Ca sites of the HAp NPs (Fig. 15(a)).…”
Section: Photofunctionalizationmentioning
confidence: 99%
“…According to previous reports, the coordination environment of Eu 3+ ions in Eu:HA may be changed through the interaction with organic molecules. Citric acid (Cit) is an organic acid containing three carboxyl groups with a strong coordination ability (i.e., formation of the chelates) with various metal ions, which can effectively coordinate with lead­(II) and cadmium­(II) ions , and can also coordinate with calcium­(II), terbium­(III), and europium­(III) ions for immobilizing various crystal surfaces. In addition, the inhibition of crystal growth and the enhancement of crystal solubility occurred through the coordination effect, and the dissolution–reprecipitation processes of the crystals are strongly related to ion replacement. , Moreover, it was suggested that Cit coordination could promote the replacement state change of Eu 3+ ions in HA. Furthermore, our group has elucidated the interactions between Cit and Eu:HA, which suppressed the photoluminescence (PL) deactivation caused by the adsorption of surface water molecules. Thus, the control of the Cit coordination behavior can change the PL properties of the Eu 3+ ions in HA.…”
Section: Introductionmentioning
confidence: 99%